2023
DOI: 10.3389/fendo.2023.1181941
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lipid accumulation product and new-onset diabetes in the Japanese population: a retrospective cohort study

Abstract: BackgroundDiabetes has become a global public health problem. Obesity has been established as a risk factor for diabetes. However, it remains unclear which of the obesity indicators (BMI, WC, WhtR, ABSI, BRI, LAP, VAI) is more appropriate for monitoring diabetes. Therefore, the objective of this investigation is to compare the strength of the association of these indicators and diabetes and reveal the relationship between LAP and diabetes.Methods15,252 people took part in this research. LAP was quartered and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Visceral adiposity index (VAI) and waist/height ratio (WHtR) [20,40]. Similarly, the present study also showed that LAP (AUC = 0.66) has higher diagnostic value than WC (AUC = 0.60) and TG (AUC = 0.64).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Visceral adiposity index (VAI) and waist/height ratio (WHtR) [20,40]. Similarly, the present study also showed that LAP (AUC = 0.66) has higher diagnostic value than WC (AUC = 0.60) and TG (AUC = 0.64).…”
Section: Discussionsupporting
confidence: 74%
“…The association between LAP and T2DM has been found to be positive in several demographic and ethnic subgroups. Brie y, in the Japanese population, high LAP have been shown to increase the risk of T2DM by 76% over time [20]. Similar results have been reported in adults Chinese and middle-aged Koreans [27,28].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…LAP has emerged as a promising anthropometric index for assessing cardiometabolic risk ( 31 , 34 ). Evidence showed that LAP serves as a predictor of diabetes risk in both Japanese and Chinese populations, outperforming traditional obesity indicators ( 35 , 36 ). A population-based prospective cohort study conducted in China revealed that individuals in the high LAP group had a 1.67 times higher risk of stroke compared to those in the low LAP group ( 37 ).…”
Section: Discussionmentioning
confidence: 99%